LDPC Codes Based on α-Resolvable Designs - Saurabh, Shyam; Sinha, Kishore (SN computer science, 2023)
Earlier regular low-density parity-check (LDPC) codes have been constructed using resolvable combinatorial designs. Here we have constructed LDPC codes from α -resolvable ( α > 1) designs which are generalization of resolvable designs. The LDPC codes obtained here from α -resolvable ( α > 1) designs have much higher code rate in comparison to the earlier codes for the same code length but constructed from resolvable designs.